Disentangling the process of epistemic change: The role of epistemic volition. (29th July 2020) - Kerwer, Martin; Rosman, Tom; Wedderhoff, Oliver; Chasiotis, Anita
Abstract : Background: Many interventions on epistemic beliefs (i.e., individual beliefs about knowledge and knowing) are based on Bendixen and Rule's Integrative Model for Personal Epistemology Development . Empirically, however, the model is still insufficiently validated. This is especially true for its epistemic volition component – a will or desire to actively change one's beliefs. Aims: To experimentally scrutinize the role of epistemic volition, we investigated (incremental) effects on epistemic change of an epistemic volition intervention. Sample: 412 psychology students enrolled at German universities completed the study. Methods: We employed a randomized pre–post design with three experimental groups that differed in the administered epistemic volition and resolvable controversies interventions. The purpose of the latter was to initiate an epistemic change process, thereby laying the foundation for the epistemic volition intervention. Both data collection and interventions were conducted online. In addition to self‐report measures, we applied a complementary source evaluation task to analyse epistemic change. Results: Even though we found small‐ to medium‐sized changes in epistemic beliefs, these changes did not differ between experimental conditions. Exploratory analyses suggested, however, that source evaluation task performance might have been promoted by the epistemic volition intervention and that – across experimental groups – manipulation check measures on both interventions interacted positively. Conclusion: Ultimately, we failed to separate the effects that our epistemic volition intervention had on epistemic change from these of the resolvable controversies intervention. Nonetheless, our study makes some strong contributions to – and interconnects – the growing bodies of research on epistemic change and multiple source use.